Copper-catalyzed condensation reactions for the synthesis of multisubstituted heteroarenes - Tan, Simon Wei Wen (2017)
Heteroarenes are ubiquitously found in many biologically active natural and man made products such as pharmaceuticals, polymeric materials, and are also essential building blocks for the synthesis of complex molecules. Thus, the efficient and regioselective synthesis of heteroaromatic compounds has been one of the main topics of interest for organic, medicinal and material chemists. Over the past decades, transition metal catalysts have emerged to be attractive and powerful tools to enable heteroarene synthesis with a broad functional group compatibility and unique reaction patterns, thus complementing the limitations of classical synthetic methods. This thesis describes the development of new copper-catalyzed condensation methods for the synthesis of highly substituted heteroarenes such as pyrroles, furans, thiophenes, and pyridines. Following the general introduction described in Chapter 1, Chapter 2 describes a copper-catalyzed condensation of imines and diazocarbonyl compounds to afford highly substituted pyrroles, which is also applicable to the synthesis of lamellarin family of natural products. Chapter 3 describes an extension of the method developed in Chapter 2, that is, a copper-catalyzed condensation of 2-siloxy-1-alkenes and diazocarbonyl compounds into highly substituted 2-siloxy-2,3-dihydrofurans. The 2 siloxy-2,3-dihydrofurans serve as versatile surrogates for the preparation of furans, pyrroles and thiophenes in one-pot. In Chapter 4, we have established a copper-catalyzed condensation of O-acetyl oximes and α,β-unsaturated imines to afford highly substituted pyridines. The reactions developed herein commonly feature simple and low cost catalytic systems, broad functional group tolerance, regioselective formation of highly substituted heteroarenes starting from readily available starting materials.